2019
DOI: 10.1177/0969141319864398
|View full text |Cite
|
Sign up to set email alerts
|

Return to bowel screening after a false-positive faecal immunochemical test in BowelScreen (the National Bowel Screening Programme in Ireland)

Abstract: Objective Little research exists on what predicts individual return to screening after a false-positive faecal immunochemical test in a population bowel screening programme. We aimed to quantify the impact of false-positive faecal immunochemical test in the first round of screening on re-attendance in BowelScreen, the National Bowel Screening Programme in Ireland. Methods A retrospective cohort study was conducted. False-positivity was defined as a positive faecal immunochemical test with subsequent colonoscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Twelve studies investigated incidence differences ( Table 2 ) ( Balhareth et al, 2018 , Clarke et al, 2014 , Donnelly et al, 2013 , McDevitt et al, 2017 , National Cancer Registry Ireland, 2018a , National Cancer Registry Ireland, 2022a , O'Brien and Sharp, 2013 , Sharp et al, 2014 , Ullah et al, 2018 , Walsh et al, 2016 ). Twenty-four investigated differences in screening participation ( All Ireland Traveller Health Study Team, 2010 , Barrett et al, 2011 , Central Statistics Office, 2020 , Ch'ng et al, 2019 , Clarke et al, 2016 , Codd et al, 1994 , Connolly and Whyte, 2019 , Fitzpatrick et al, 2011 , Fleming et al, 2013 , Gallagher and Gallagher, 2010 , Lalor and Redmond, 2009 , McCarron et al, 2011 , McNamara et al, 2014 , McNamara et al, 2011 , Moore et al, 2017 , National Screening Service, 2020a , National Screening Service, 2020b , National Screening Service, 2021 , National Screening Service, 2022 , Ní Riain et al, 2001 , O'Brien et al, 2018 , Pavee Point Traveller and Roma Centre & Mid West Traveller Health Unit, 2019 , Walsh et al, 2010 , Walsh et al, 2012 ). Twenty studies reported on breast cancer, 16 on colorectal cancer and 15 on cervical cancer.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Twelve studies investigated incidence differences ( Table 2 ) ( Balhareth et al, 2018 , Clarke et al, 2014 , Donnelly et al, 2013 , McDevitt et al, 2017 , National Cancer Registry Ireland, 2018a , National Cancer Registry Ireland, 2022a , O'Brien and Sharp, 2013 , Sharp et al, 2014 , Ullah et al, 2018 , Walsh et al, 2016 ). Twenty-four investigated differences in screening participation ( All Ireland Traveller Health Study Team, 2010 , Barrett et al, 2011 , Central Statistics Office, 2020 , Ch'ng et al, 2019 , Clarke et al, 2016 , Codd et al, 1994 , Connolly and Whyte, 2019 , Fitzpatrick et al, 2011 , Fleming et al, 2013 , Gallagher and Gallagher, 2010 , Lalor and Redmond, 2009 , McCarron et al, 2011 , McNamara et al, 2014 , McNamara et al, 2011 , Moore et al, 2017 , National Screening Service, 2020a , National Screening Service, 2020b , National Screening Service, 2021 , National Screening Service, 2022 , Ní Riain et al, 2001 , O'Brien et al, 2018 , Pavee Point Traveller and Roma Centre & Mid West Traveller Health Unit, 2019 , Walsh et al, 2010 , Walsh et al, 2012 ). Twenty studies reported on breast cancer, 16 on colorectal cancer and 15 on cervical cancer.…”
Section: Resultsmentioning
confidence: 99%
“…Participation was higher in the 50–59 age group compared to the 60 + age group.Cervical: in all ages, 22.7% reported attending for cervical screening in the last 12 months compared to 11.6% from the medical card population in the SLAN study. AACODS, high ( Ch'ng, Mooney, O'Donoghue, & Fitzpatrick, 2019 ) Individuals aged 60–69 who received a negative (n = 105,276) or false-positive (n = 1,999) FIT (colorectal screen) in Ireland. To quantify the impact of false-positive FIT in the first round of screening on re-attendance in colorectal screening.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation